PENGEMBANGAN MODUL MENULIS BERBASIS MULTIPLE INTELLIGENCES PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VII SMP AL-AZHAR MEDAN - Wita Dwi Payana (Jurnal Bahastra, 2021)
This study aims to determine: (1) the arranging of teaching modul based writing multiple intelligences, (2) the feasibility of teaching modul based writing multiple intelligences, (3) the effectiveness of teaching modul based writing multiple intelligences for students of VII grade at SMP Al-Azhar Medan. Kind of this research is a research and development based on the model of Borg and Gall. Subject trials consist of subject experts, design experts, Indonesian teachers, students of SMP Al-Azhar Medan on individual testing consisted of three students, 9 students in small group trial, and 32 students in the confined field group trials. Data of the quality of product development is collected through questionnaires. The results showed that: (1) validation of the content experts include the feasibility of content with an average of 92,19% in very good criteria, eligibility presentation with an average of 100% in the very well criteria, aspects multiple intelligences with an avarege 96,87%, and aspects of language with an average of 91,66% in the very well criteria, (2) validation of design experts with an average of 84,35% in the very well criteria, (3) individual testing with an average of 85,00% with a very good criteria, (4) the trial of small group with an average of 91,94% with a very good criteria, and (5) a limited field test groups with an average of 94,99% with a very good criteria, (6) the effectiveness of instructional materials with a presentation by 76,75% with good criteria , Thus, the development of module based writing multiple intelligences learning Indonesian that have been developed is proper to use in the learning process as a learning resource.